2010
DOI: 10.1371/journal.pone.0009865
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Estimation of the Robustness Region of Biological Models with Oscillatory Behavior

Abstract: Robustness is an essential feature of biological systems, and any mathematical model that describes such a system should reflect this feature. Especially, persistence of oscillatory behavior is an important issue. A benchmark model for this phenomenon is the Laub-Loomis model, a nonlinear model for cAMP oscillations in Dictyostelium discoideum. This model captures the most important features of biomolecular networks oscillating at constant frequencies. Nevertheless, the robustness of its oscillatory behavior i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Stochastic simulations showed that noise can extend the Hopf bifurcation point in both single-(F 31 ) and dual-feedback systems (F 31,32 ), producing oscillations at parameter values that does not lead to oscillations in a deterministic setting. Comparing the bifurcation points in F 31 and F 31,32 at different levels of the inner loop showed that the points were not altered, suggesting that addition of the second loop in the nested arrangement had no effect on the stochastic bifurcation points. Further understanding concerning the interplay between noise and oscillations in coupled-feedback settings should be among the focuses of future systems biology studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stochastic simulations showed that noise can extend the Hopf bifurcation point in both single-(F 31 ) and dual-feedback systems (F 31,32 ), producing oscillations at parameter values that does not lead to oscillations in a deterministic setting. Comparing the bifurcation points in F 31 and F 31,32 at different levels of the inner loop showed that the points were not altered, suggesting that addition of the second loop in the nested arrangement had no effect on the stochastic bifurcation points. Further understanding concerning the interplay between noise and oscillations in coupled-feedback settings should be among the focuses of future systems biology studies.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate analytical treatment, we instead employ the Routh -Hurwitz theorem [29,30] which states that the eigenvalues, essentially the roots of the characteristic polynomial jJ 2 lIj 31,21 . To verify that (2.4) also constitute the sufficient condition for oscillations in these systems, we employed analysis based on the Floquet theory that globally assesses the stability of the obtained periodic solutions [31][32][33]. The mathematical and computational background of the Floquet analysis is given in the electronic supplementary material.…”
Section: ð2:3þmentioning
confidence: 99%
See 1 more Smart Citation
“…During aggregation stage of development, Dictyostelium cells show spontaneous oscillations and chemotactic movement that are correlated with periodic changes in the extracellular cAMP concentrations. The molecular network regulating these oscillations has been studied [41,42] . The oscillations in external cAMP ( X 6 ) concentration and intracellular cAMP ( X 5 ) concentration are maintained by periodic activation and deactivation of regulatory units, viz.…”
Section: Camp Oscillations In Chemotactic Dictyostelium Discoideum Cellsmentioning
confidence: 99%
“…, regulation of cAMP oscillations in Dictyostelium discoideum ( Section 3.2 ) and regulation of circadian oscillations in Drosophila ( Section 3.3 ) are next described. The cAMP oscillation model used in Section 3.2 has a known S-system representation [41,42] while the circadian oscillations model used in Section 3.3 follows a Michaelis-Menten and Hill type kinetics [43] . It would be interesting to see if an acceptable S-system model with an identified structure can be obtained by ETFGA especially when the true system phenomenology is different.…”
Section: Introductionmentioning
confidence: 99%